Long‐term impact of a behavioral weight management program on depression and anxiety symptoms: 5‐year follow‐up of the WRAP trial. Issue 12 (27th October 2022) - Jones, Rebecca A.; Mueller, Julia; Sharp, Stephen J.; Griffin, Simon J.; Ahern, Amy L.
Abstract: Objective: Behavioral weight management programs may support short‐term mental health; however, limited evidence reports the long‐term impacts. This study investigated the impact of behavioral weight management programs on depression and anxiety symptoms at 5 years from baseline. Methods: The Weight loss Referrals for Adults in Primary care (WRAP) trial randomized 1267 adults with BMI ≥ 28 kg/m 2 to a brief intervention (BI) or commercial behavioral weight management program (WW; formerly Weight Watchers) for 12 or 52 weeks (CP12 and CP52, respectively). Linear regression was used to separately compare 5‐year changes in depression and anxiety symptoms (by Hospital Anxiety and Depression Scale) between randomized groups, adjusting for baseline depression/anxiety symptoms, gender, and research center. Results: A total of 643 (51%) participants attended the 5‐year study follow‐up visit. There was no evidence of a difference between the randomized groups for 5‐year changes in depression (BI: −0.08 ± 3.29; CP12: 0.02 ± 3.01; CP52: −0.09 ± 3.41) or anxiety (BI: 0.16 ± 3.50; CP12: −0.05 ± 3.55; CP52: −0.66 ± 3.59) symptoms. Conclusions: This study found no evidence that commercial weight management programs differed in 5‐year changes in depression and anxiety symptoms, compared with BI. These are average effects; some individuals experienced increases or decreases in symptoms. Future research should investigate who is at most risk of mental health declines and investigate how to support them. Future trials should transparently report long‐term mental health outcomes to strengthen understanding.